The life of Chuck - King, Stephen, 1947- (Scribner, 2025)
"In a crumbling world plagued by natural disasters, collapsing infrastructure, and mass panic, bizarre billboards and advertisements appear throughout town: "Charles Krantz. Thirty-nine great years. Thanks, Chuck!" Marty Anderson, a schoolteacher, becomes obsessed with these messages as the world, inexplicably linked to Chuck's life, seems to be approaching its end. Told in three acts, presented in reverse order, The Life of Chuck explores one man's past. We see him in middle age on a business trip in Boston as he is seduced by a busker into spinning a gorgeous sidewalk dance. And we see him as a child, in a house haunted by a terrible secret, learning to dance with his grandmother. In these pages King reminds us that life's quotidian pleasures are even more glorious because they are fleeting: the outrageous good fortune of a beautiful blue day after a string of gray ones; the delight of dancing when every move feels perfect; a serendipitous meeting. King's ability to describe pure joy rivals his ability to terrify us." --